Identification of hypoglycin A binding adsorbents as potential preventive measures in co‐grazers of atypical myopathy affected horses. (4th September 2017) - Krägeloh, T.; Cavalleri, J. M. V.; Ziegler, J.; Sander, J.; Terhardt, M.; Breves, G.; Cehak, A.
Summary: Background: Intestinal absorption of hypoglycin A (HGA) and its metabolism are considered major prerequisites for atypical myopathy (AM). The increasing incidence and the high mortality rate of AM urgently necessitate new therapeutic and/or preventative approaches. Objectives: To identify a substance for oral administration capable of binding HGA in the intestinal lumen and effectively reducing the intestinal absorption of the toxin. Study design: Experimental in vitro study. Methods: Substances commonly used in equine practice (activated charcoal composition, di‐tri‐octahedral smectite, mineral oil and activated charcoal) were tested for their binding capacity for HGA using an in vitro incubation method. The substance most effective in binding HGA was subsequently tested for its potential to reduce intestinal HGA absorption. Jejunal tissues of 6 horses were incubated in Ussing chambers to determine mucosal uptake, tissue accumulation, and serosal release of HGA in the presence and absence of the target substance. Potential intestinal metabolism in methylenecyclopropyl acetic acid (MCPA)‐conjugates was investigated by analysing their concentrations in samples from the Ussing chambers. Results: Activated charcoal composition and activated charcoal were identified as potent HGA binding substances with dose and pH dependent binding capacity. There was no evidence of intestinal HGA metabolism. Main limitations: Binding capacity of adsorbents was tested in vitro using aqueous solutions, and in vivo factors such as transit time and composition of intestinal content, may affect adsorption capacity after oral administration. Conclusions: For the first time, this study identifies substances capable of reducing HGA intestinal absorption. This might have major implications as a preventive measure in cograzers of AM affected horses but also in horses at an early stage of intoxication.